PRODUCT ATTRIBUTE PREFERENCES – A MULTIDISCIPLINARY APPROACH - Veres, Zoltan; Tarjan, Tamas; Hamornik, Balazs Peter (European Scientific Journal, ESJ, 2014)
The basis of buyers’ preferences are the differences of goods. Revealed preferences can be deducted from the market behaviour of the consumers, that is from their choices. In marketing consumer preferences are defined as the subjective tastes, as measured by utility, of various bundles of goods. They permit the consumer to rank these bundles of goods according to the levels of utility they give the consumer. In an expert brainstorming process we have identified eight factors that can determine the perception of product attributes: attribute strengths, preference interval, stability, product complexity, consumer task, lifelikeness, environment and experience. Our series of research plans to analyse the perception of product attributes and the system of the parameters of preferences related to them in a complex way. We aim to investigate preference systems that relate to the system of attributes with a multidisciplinary, multifocus, hierarchic series of surveys. As a first stage in our experimental study we are investigating intransitivity occurring in participants’ preferences during selection between simple, medium complex, and complex products. The participants’ task is to make pair-wise comparisons of preference between specific realizations of each product group. There are two possible versions to show up the pairs of virtual products to the subjects. We show up to the subject those attributes, which are not different, then only those that are different from each other. Using a computer based experimental design every participant has the personalized attribute set.